1970
DOI: 10.1177/001440297003600505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Teacher Attention and a Token Reinforcement System in a Junior High School Special Education Class

Abstract: Teacher attention and a token reinforcement system were used to bring about control in a disruptive junior high school special education classroom. Individual and group study levels were recorded during a baseline period. Subsequent experimental periods employing teacher attention and/or a token point system increased study levels and decreased disruptive behaviors of class members. Reinforcement of appropriate behaviors was withdrawn during short reversals producing lowered study rates. Reinstatement of conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

1972
1972
1998
1998

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…PREVIOUS STUDIES (1,2,4,5) have demonstrated that children's behavior can be systematically and scientifically modified within the public schools. In a maj ority of the studies the classroom teacher delivered either social or tangible reinforcement for appropriate student behavior.…”
mentioning
confidence: 99%
“…PREVIOUS STUDIES (1,2,4,5) have demonstrated that children's behavior can be systematically and scientifically modified within the public schools. In a maj ority of the studies the classroom teacher delivered either social or tangible reinforcement for appropriate student behavior.…”
mentioning
confidence: 99%
“…In other words, all who participate in the appropriate or inappropriate activity participate in its consequences. Classic research (e.g., Barrish, Saunders, & Wolf, 1969;Broden, Hall, Dunlap, & Clark, 1970;Sulzbacher & Houser, 1968) has demonstrated the efficacy of the interdependent group contingency to manage student behavior and establish an environment of discipline. Additionally, this technique has been recommended for use in cooperative learning teams to minimize disruptive group behavior (Maurer, 1988).…”
Section: Interdependent Group Contingencymentioning
confidence: 99%
“…While the viability of extrinsic reinforcement for providing short-term motivation is apparent, it should be the goal of any behavior management program to ultimately fade out the extrinsic contingencies and turn to an internal reward system. Several studies have used extrinsic token systems in educational settings (Broden, Hall, Dunlap, & Clark, 1970;O'Leary & Becker, 1967). It does not appear, however, that any study has demonstrated control of behavior by (a) an extrinsic reinforcement system, (b) fading the extrinsic system while employing a self-management program based on an intrinsic reinforcement system, and (c) maintaining the self-managed behavior over time and across settings.…”
Section: Self-managementmentioning
confidence: 99%